MEWUJUDKAN KEADILAN ADMINISTRATIF: ANALISIS HUKUM ACARA PERADILAN TATA USAHA NEGARA DI INDONESIA - Ritonga, Joni Sandri; Puspita, Amalia Dwi; Ardiani, Cyntia Febri; Dewi, Elma Puspita; Wardina, Kayla Nazwa; Hasanah, Melia Dwi; Husaini, Nur Jihan (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The State Administrative Court (PTUN) has a very important role in the Indonesian legal system, especially in providing administrative justice for people who feel aggrieved by government decisions or actions. This journal aims to analyze the procedural law of the state administrative court in Indonesia, starting from the procedure to its role in maintaining administrative justice. The discussion began with an explanation of the legal basis of the PTUN, the scope of cases that can be handled, and the procedures that apply in resolving state administrative disputes. Furthermore, this journal analyzes the legal effectiveness of the PTUN procedure, its advantages and disadvantages, as well as its contribution to the protection of human rights and legal certainty. Through case studies and comparisons with administrative justice systems in other countries, it was found that although the PTUN has some weaknesses, its function in providing legal protection to individuals and legal entities is very important. For this reason, improvements are needed in procedures so that the PTUN is more effective in resolving administrative disputes, as well as providing a more optimal sense of justice for the community